The Effect of Fintech Payment and Financial Literacy on Impulsive Buying of college students in Medan City - Pakpahan, Dewi Rapiah; Cici Handayani; Mega Sanjaya (Journal of Finance Integration and Business Independence, 2024)
This study aims to determine the effect of Fintech Payment and Financial Lit-eration on Impulsive Buying of students in Medan City. The research method used is a descriptive method with a quantitative approach. This descriptive method involves collecting data to test hypotheses or answer questions about people's opinions on an issue or topic. The population in this study were 6th semester students from 8 universities in Medan City totaling 3700 students, the sampling technique used a quota sample with sample determination using the Slovin formula which amounted to 361 students who were sampled in this study. In this study, the authors used Partial Least Square (PLS) data analysis techniques. PLS is a statistical data analysis method that analyzes independent variables (exogenous) and dependent variables (endogenous) simultaneously. The results showed that directly Fintech payment has a positive and significant effect on impulsive buying on students in Medan City with a tcount> ttable value of 2.312 > 1.98 and a pvalue of 0.021 < 0.05. Directly Financial literacy has no positive and insignificant effect on impulsive buying on students in Medan City with a tcount > ttable value of 1.601 < 1.98 and a pvalue of 0.055 > 0.05. Directly Fintech Payment and Financial literacy have a positive and significant effect on Impulsive buying on students in Medan City with a tcount> ttable value of 3.048 > 1.98 and a pvalue of 0.008 < 0.05. This research is expected to provide deeper insight into the consumption behavior of students, especially related to the use of fintech payments. By understanding the factors that influence impulsive buying, universities and educational institutions can design more effective educational programs to improve financial literacy among students